The challenges of learning and teaching chemical bonding at different school levels using electrostatic interactions instead of the octet rule as a teaching model. Issue 3 (21st June 2018) - Joki, Jarkko; Aksela, Maija
Abstract : Teaching chemical bonding using the octet rule as an explanatory principle is problematic in many ways. The aim of this case study is to understand the learning and teaching of chemical bonding using a research-informed teaching model in which chemical bonding is introduced as an electrostatic phenomenon. The study posed two main questions: (i) how does a student's understanding of chemical bonding evolve from lower- to upper-secondary school when an electrostatic model of chemical bonding was used at the lower-secondary level? (ii) How does the teaching of octets/full shells at the upper-secondary level affect students' understanding? The same students were interviewed after lower-secondary school and again during their first year at upper-secondary school. Their upper-level chemistry teachers were also interviewed. The interview data were analysed using the grounded theory method. The findings showed that the students' earlier proper understanding of the electrostatic-interactions model at the lower-secondary level did not prevent the later development of less-canonical thinking. Teachers' pedagogical content knowledge (PCK) of the explanatory principles of chemical bonding and how to use explanations in science education needs to be promoted in both pre-service teacher education and during in-service training.